FernGully : the last rainforest [videorecording (DVD)] (20th Century-Fox family feature., 2009)
Magic and adventure await in FernGully, a spectacular rainforest where a bat named Batty, whose radar has gone haywire, joins together with Crysta, Pips and the Beetle Boys to save their marvelous world from the evil Hexxus.